Study on the Consciousness of Sex and the Attitudes of Homosexuality in Students Majoring in Health Care (Medico Legal Update, 2019)
College students majoring in health care who will lead the future health community studied consciousnessof sex, attitudes toward homosexuality and acceptance of homosexuality. From March 5 to 15, 2018, theprogram was conducted for students majoring in health education who are attending a four-year universitylocated in South Chungcheong Province. First, the purpose and procedure of the study were described andagreed upon by students, and the results of the survey were analyzed using the SPSS statistics program.Research shows that sexual consciousness, attitudes toward homosexuality and acceptance of homosexualitydiffered a lot according to demographic characteristics. Correlations have shown that students who are openmindedabout sex have a positive attitude toward homosexuality and have high acceptance of homosexuality.A proper education is needed based on the results of the study, as the values and behaviors of incorrect sexcan lead to a lot of confusion and physical damage.